Simulated geomagnetic reversals and preferred virtual geomagnetic pole paths - Kutzner, C.; Christensen, U. R. (Geophysical Journal International, 2004)
The question of whether virtual geomagnetic poles (VGPs) recorded during reversals and excursions show a longitudinal preference is a controversial one amongst palaeomagnetists. One possible mechanism for such VGP clustering is the heterogeneity of heat flux at the core—mantle boundary (CMB). We use 3-D convection-driven numerical dynamo models with imposed non-uniform CMB heat flow that show stochastic reversals of the dipole field. We calculate transitional VGPs for a large number of token sites at the Earth's surface. In a model with a simple heat flux variation given by a Y 22 harmonic, the VGP density maps for individual reversals differ substantially from each other, but the VGPs have a tendency to fall around a longitude of high heat flow. The mean VGP density for many reversals and excursions shows a statistically significant correlation with the heat flow. In a model with an imposed heat flux pattern derived from seismic tomography we find maxima of the mean VGP density at American and East Asian longitudes, roughly consistent with the VGP paths seen in several palaeomagnetic studies. We find that low-latitude regions of high heat flow are centres of magnetic activity where intense magnetic flux bundles are generated. They contribute to the equatorial dipole component and bias its orientation in longitude. During reversals the equatorial dipole part is not necessarily dominant at the Earth's surface, but is strong enough to explain the longitudinal preference of VGPs as seen from different sites.